Gently steering - the mechanism of how motivational interviewing supported walking after hip fracture: A qualitative study - Made U. Rimayanti; Nicholas F. Taylor; Paul D. O'Halloran; Nora Shields (Elsevier, 2022)
Objective: To explore how older adults perceive motivational interviewing influences their walking and physical activity after hip fracture. Methods: Qualitative study using an interpretive description framework. Twenty-four participants aged ≥65 years living in the community after hip fracture were interviewed. Participants had received at least 8 sessions of motivational interviewing via telephone. Semi-structured interviews were transcribed verbatim and coded inductively by two researchers independently. All authors discussed findings and themes observed through the researchers' lens and mapped them to the Medical Research Council's framework for process evaluation. Results: Motivational interviewing was described as a nuanced and subtle intervention that guided participants through their journey of recovery. Three themes described possible mechanisms of how motivational interviewing might work: connection, checking in and confidence. In the context of recovering from hip fracture psychologically and physically, a strong connection with clinicians, along with weekly checking in, were perceived to build participants' confidence to walk after hip fracture. Conclusion: This study provided insight on participant perceptions of how motivational interviewing might work to support walking after hip fracture. Innovation: The addition of motivational interviewing to rehabilitation is a novel way of building confidence to walk for people recovering from hip fracture.